Rezension von: Mihailescu, Peter-Michael; Michalke, Matthias, Vergessene Bahnen in Baden Württemberg - Müller, Stefan (Württembergisch Franken, 1987)
Peter-Michael Mihailescu und Matthias Michalke: Vergessene Bahnen in Baden-Württemberg. Stuttgart: Theiss 1985. 270 S., 180 Abb.